Fears of Psychological Treatment and Attitudes Towards Seeking Professional Help Among Students - Chai, Ming Sing (2000)
The rate of utilisation of the counseling and guidance services in schools is minimal in spite of the availability of these services No extensive studies have been done in Malaysia to show the relationship of factors that are related to psychological help-seeking among school students The present study is a combination of correlational and causal-comparative research The relationships of fears of psychological treatment, attitudes towards seeking professional psychological help, and the likelihood of seeking counseling were investigated besides that, the differences in terms of sex, ethnicity, prior contact With a counsellor and help seeking history With regards to the three variables mentioned earlier were also examined .